2018
DOI: 10.3390/molecules23123141
|View full text |Cite
|
Sign up to set email alerts
|

Monomyristin and Monopalmitin Derivatives: Synthesis and Evaluation as Potential Antibacterial and Antifungal Agents

Abstract: In the present work, monoacylglycerol derivatives, i.e., 1-monomyristin, 2-monomyristin, and 2-monopalmitin were successfully prepared from commercially available myristic acid and palmitic acid. The 1-monomyristin compound was prepared through a transesterification reaction between ethyl myristate and 1,2-O-isopropylidene glycerol, which was obtained from the protection of glycerol with acetone, then followed by deprotection using Amberlyst-15. On the other hand, 2-monoacylglycerol derivatives were prepared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…The other chemicals such as urea, potassium hydroxide, sulfuric acid, Amberlyst-15 and Thermomyces Lanuginosa as Lipase enzyme were purchased in pro analytic grade and used without further purification. The synthesis of 1,2- O -isopropylidene glycerol has been carried out in a similar procedure to the previously described 25 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other chemicals such as urea, potassium hydroxide, sulfuric acid, Amberlyst-15 and Thermomyces Lanuginosa as Lipase enzyme were purchased in pro analytic grade and used without further purification. The synthesis of 1,2- O -isopropylidene glycerol has been carried out in a similar procedure to the previously described 25 .…”
Section: Methodsmentioning
confidence: 99%
“…The antimicrobial assay of the synthesized products was carried out at Microbiology Laboratory of Faculty of Veterinary Medicine, Universitas Gadjah Mada by using a well-diffusion method as previously reported 25,27 . S. aureus FNCC 0047 was used as a representative of gram-positive bacteria while E. coli FNCC 0091 was used as a representative of gram-negative bacteria.…”
Section: Methodsmentioning
confidence: 99%
“…The antibacterial and antifungal activity assays were conducted to evaluate the biological activity of the synthesized product according to the method that has been previously described [24]. The bacteria used were S. aureus and B. subtilis for the gram-positive bacteria, and S. typhimurium and E. coli for the gram-negative bacteria, while C. albicans was selected for antifungal assay.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, monomyristin derivatives of sugars show higher antibacterial activities against S. aureus , E. coli , B. subtilis and Aggregatibacter actinomycetemcomitans ( A. actinomycetemcomitans ). It was found that a 1-monomyristin derivative exhibits higher antifungal activity against C. albicans than a monopalmitin derivative [24]. Furthermore, the lauric esters of monosaccharide also exhibited medium antifungal and antibacterial activity against gram-positive bacteria [25].…”
Section: Introductionmentioning
confidence: 99%
“…As Indonesia has 10% of world plant species in 90 ecosystems [3], Indonesia becomes the second largest mega biodiversity country in the world. Because of these abundant natural resources, researches on the isolation and application of tropical plants and fruits have gained a lot of interest [4][5][6].…”
Section: Introductionmentioning
confidence: 99%